Pattern of iron profile in type 2 diabetes mellitus patients: experience from outpatient department of Bangladesh Diabetic Network (BIRDEM Medical Journal, 2022)
Background: Worldwide diabetes mellitus (DM) has been recognized as the most prevalent endocrine disorder. Excess iron has been implicated in the pathogenesis of diabetes and its complications. Iron is a transitional metal and a potential catalyst in cellular reaction that produces reactive oxygen species. Free iron causes the assembly of reactive oxygen species that invariably steer the body’s homeostasis towards oxidative stress-mediated diabetic complications. On the other hand, ferritin is an index of body iron stores and acts as an iron overload marker. Elevated iron indices are more common in patients with diabetes. Excess iron may have a role in the development of diabetes and subsequently in glycemic control. In this context, this study was aimed to assess the pattern of plasma iron profile in type 2 DM patients and compare with healthy controls.Methods: This cross-sectional study included 284 subjects attending the outpatient department of Endocrinology of Bangladesh Diabetic Network Ltd. (BDN) from January 2021 to June 2021. This study was done to evaluate the serum iron, total iron binding capacity (TIBC) and ferritin of 284 subjects divided into two groups (I and II) of 182 Type 2 DM patients constituted Group I and Group II consisted of 182 healthy individuals (controls).Results: Mean serum free iron concentration in Group I and Group II were 14.24± 6.7 and 11.29±4.1 ìmol/ l respectively. Mean TIBC in Group I and Group II were 54.19 ±9.8 and 64.08±7.5 ìmol/l respectively. However, mean serum ferritin concentration were 169.50±15.1and 121.29±11.9 mg/ml respectively. The difference between serum iron, TIBC and ferritin between Group I and Group II were highly significant with the p values 0.003, 0.016 and 0.042 respectively. In Group I, glycated hemoglobin (HbA1c) and fasting blood glucose levels both increased. However In this investigation, HbA1c levels were found to have a substantial relationship with serum iron levels and TIBC. However, there was no significant link between serum ferritin and HbA1c.Conclusion: The results obtained from this study suggests that serum iron and serum ferritin were increased and TIBC was decreased in T2DM patients as compared to healthy control. In patients with T2DM, there was a potentiated disparity in the readings. The findings suggest that these micronutrient levels can be employed as biomarkers for T2DM patients.BIRDEM Med J 2022; 12(2): 124-128